2007
DOI: 10.1088/0953-8984/19/32/322201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric field on one-dimensional insulators: a density matrix renormalization group study

Abstract: We perform density matrix renormalization group (DMRG) calculations extensively on one dimensional Mott and Peierls chains with explicit inclusion of the static bias to study the insulator-metal transition in those systems. We find that the electric field induces a number of insulator-metal transitions for finite size systems and at the thermodynamic limit, the insulating system breaks down into a completely conducting state at a critical value of bias which depends strongly on the insulating parameters. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
17
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 34 publications
7
17
0
Order By: Relevance
“…We found that electric fields as low as 2 kV/cm induce an electronic phase change in these compounds from a Mott insulating state to a metallic-like state. Our results suggest that this transition belongs to a new class of resistive switching and might be explained by recent theoretical works predicting that an insulator to metal transition can be achieved by a simple electric field in a Mott Insulator [3,4,5] . This new type of resistive switching has potential to build up a new class of Resistive Random Access Memory (RRAM) with fast writing/erasing times (50 ns to 10 µs) and resistance ratios R/R of the order of 25% at room temperature.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…We found that electric fields as low as 2 kV/cm induce an electronic phase change in these compounds from a Mott insulating state to a metallic-like state. Our results suggest that this transition belongs to a new class of resistive switching and might be explained by recent theoretical works predicting that an insulator to metal transition can be achieved by a simple electric field in a Mott Insulator [3,4,5] . This new type of resistive switching has potential to build up a new class of Resistive Random Access Memory (RRAM) with fast writing/erasing times (50 ns to 10 µs) and resistance ratios R/R of the order of 25% at room temperature.…”
supporting
confidence: 62%
“…Conversely, RRAM based on an Electronic Phase Change are still experimentally unexplored, while they could offer more reliability and higher speed [6,7] . In that respect, the recent theoretical prediction that a simple electric field could drive an insulator to metal transition in a Mott Insulator [3,4,5] appears as particularly appealing. It paves the way for a new type of RRAM based on an Electronic Phase Change, namely a Mott insulator-metal transition with a very fast potential switching time [9] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the experiments, the nanoscale material is an organic molecule or a π-conjugated polymer. Many theories too have been developed from empirical to semi-empirical and ab initio level to describe the electrical response functions of the nanomaterials Pati 2004, 2005;Sengupta et al 2006;Dutta et al 2007;Dutta and Pati 2008a, b).…”
Section: Introductionmentioning
confidence: 99%
“…In [9], authors performed density matrix renormalization group (DMRG) calculations to study electric field-induced insulator-metal transition in onedimensional Mott-Peierls chains. It is well established that the quantum many-body configuration interaction method captures the low-energy properties of the nanoscale systems such as graphene [10].…”
Section: Introductionmentioning
confidence: 99%